Do Silver Nanoparticles in Fixed Orthodontic Appliances Inhibit Bacterial Growth? - Kailyn Owens; Anasha Williamson; Ashley Christman, RDH, BS (Elsevier, 2024)
OBJECTIVES: The purpose of this literature review is to aid in oral hygiene instruction for clinicians with patients undergoing orthodontic treatment. METHODS: Specific criteria were required to formulate this literature review. Articles were accessed through PubMed and were peer-reviewed, original research that were published within the last five years, and relevant to the topic. Keywords for this research included orthodontics, fixed orthodontic appliances, orthodontic appliances, silver nanoparticles, silver coating, nanoparticles, bioreduction, oral bioreduction, and plaque reduction. A section from one published book was also referenced for background and comparative information. Filters for our search excluded articles posted before 2018, literature reviews, meta-analyses, or articles that were not peer reviewed. Four articles were selected to be included in this review. RESULTS: Fabricated wires, brackets, and orthodontic bands were organized into control and experimental groups. In some groups, the metal was coated with silver nanoparticles, some had zinc oxide nanoparticles, and some were left uncoated. The appliances were exposed to oral bacteria for various amount of time and then tested to see which metals accumulated the most bacteria. In one study, a combination of silver and zinc-oxide nanoparticles produced the greatest bacterial inhibition. However, each study proved silver nanoparticle coated appliances resulted in the least amount of bacterial accumulation with all bacteria tested. CONCLUSIONS: The reduction of plaque, bacteria, gingivitis, and bracket scars during and after orthodontic treatment is a direct result of silver nanoparticles and increases patient compliance to commit to an oral hygiene routine. IMPLICATIONS: Silver nanoparticles can be implemented throughout all aspects of dentistry in toothpastes, mouthwashes, and other dentifrices. Hygienists, dental professionals, and patients can benefit from the antimicrobial effects of silver nanoparticles.